Self‐Assembly of Amphiphilic Janus Dendrimers into Mechanically Robust Supramolecular Hydrogels for Sustained Drug Release. Issue 41 (1st July 2015) - Nummelin, Sami; Liljeström, Ville; Saarikoski, Eve; Ropponen, Jarmo; Nykänen, Antti; Linko, Veikko; Seppälä, Jukka; Hirvonen, Jouni; Ikkala, Olli; Bimbo, Luis M.; Kostiainen, Mauri A.
Abstract Compounds that can gelate aqueous solutions offer an intriguing toolbox to create functional hydrogel materials for biomedical applications. Amphiphilic Janus dendrimers with low molecular weights can readily form self‐assembled fibers at very low mass proportion (0.2 wt %) to create supramolecular hydrogels (G′≫G′′) with outstanding mechanical properties and storage modulus of G′>1000 Pa. The G′ value and gel melting temperature can be tuned by modulating the position or number of hydrophobic alkyl chains in the dendrimer structure; thus enabling exquisite control over the mesoscale material properties in these molecular assemblies. The gels are formed within seconds by simple injection of ethanol‐solvated dendrimers into an aqueous solution. Cryogenic TEM, small‐angle X‐ray scattering, and SEM were used to confirm the fibrous structure morphology of the gels. Furthermore, the gels can be efficiently loaded with different bioactive cargo, such as active enzymes, peptides, or small‐molecule drugs, to be used for sustained release in drug delivery.